"I did not plan to have a baby. This is the outcome of our work": a qualitative study exploring unintended pregnancy among female sex workers - Diana Faini; Patricia Munseri; Muhammad Bakari; Eric Sandström; Elisabeth Faxelid; Claudia Hanson (BMC, 2020)
Abstract Background High number of unintended pregnancies-often leading to induced abortions-are reported among female sex workers (FSWs), highlighting a major unmet need for contraception. To better understand barriers to contraceptive use, we explored FSW's pregnancy perceptions and experiences of unintended pregnancy. We hypothesized that sex work exacerbates barriers to contraceptive use and that FSW's pregnancy perceptions and experiences of unintended pregnancy influence future commitment to contraceptive use. Methods We conducted in-depth interviews with 11 FSWs (January-June 2019) in Dar es Salaam, Tanzania. We purposively sampled FSWs with a positive pregnancy test from those participating in a HIV vaccine preparedness cohort. We used open ended questions to explore how FSWs make decisions when facing barriers to contraceptive use, dealing with unintended pregnancy and adhering to contraceptive use after experiencing unintended pregnancy. All interviews were conducted in Kiswahili, audio-recorded, transcribed and translated into English. Grounded theory approach was used to analyse transcripts. Open and selective coding was performed using Nvivo software. Results FSWs reported that sex work impedes good contraceptive behaviour because sex workers felt unable to negotiate consistent condom use, avoided health services due to stigma, missed monthly contraceptive supplies because of inconvenient clinic operating hours or skipped contraceptive pills when intoxicated after taking alcohol. FSWs who perceived pregnancy to be a burden terminated the pregnancy because of fear of loss of income during pregnancy or child rearing expenses in case child support was not assured by their partners. FSWs who perceived pregnancy to be a blessing decided to keep the pregnancy because they desired motherhood and hoped that children would bring prosperity. Family planning counselling and availability of contraceptives during postpartum care influenced the initiation of contraception among FSWs. Financial hardships related to childrearing or painful abortion experiences influenced FSWs' commitment to good contraceptive practices. Conclusion Our results demonstrate that FSWs face barriers to initiating and adhering to contraceptive use because of sex work stigma, inability to negotiate condoms and failure to access medical services at their convenience. Our findings underscore the need to integrate contraceptive services with HIV programs serving FSWs in their areas of work.